2015
DOI: 10.1002/ange.201502102
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Chemoselective Aldehyde–Ketone Cross‐Couplings through the Polarity Reversal of Methylacetoin

Abstract: The thiamine diphosphate (ThDP) dependent enzyme acetoin:dichlorophenolindophenol oxidoreductase (Ao:DCPIP OR) from Bacillus licheniformis was cloned and overexpressed in Escherichia coli. The recombinant enzyme shared close similarities with the acetylacetoin synthase (AAS) partially purified from Bacillus licheniformis suggesting that they could be the same enzyme. The product scope of the recombinant Ao:DCPIP OR was expanded to chiral tertiary α‐hydroxy ketones through the rare aldehyde–ketone cross‐carboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We have recently demonstrated that Ao:DCPIP OR from Bacillus licheniformis, cloned and overexpressed in E. coli, is also capable to mediate the non-physiological 1,2-addition of methylacetoin (donor) to activated ketones (acceptors) yielding chiral tertiary α-hydroxy ketones with high efficiency (Scheme 1, route b). [24] Complete control of chemoselectivity could be achieved in this transformation due to the hitherto unreported use of methylacetoin, whose activation occurs with elimination of unreactive acetone. In addition, some of the reaction products were formed with opposite stereochemistry compared to that obtained using other ThDP-dependent enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently demonstrated that Ao:DCPIP OR from Bacillus licheniformis, cloned and overexpressed in E. coli, is also capable to mediate the non-physiological 1,2-addition of methylacetoin (donor) to activated ketones (acceptors) yielding chiral tertiary α-hydroxy ketones with high efficiency (Scheme 1, route b). [24] Complete control of chemoselectivity could be achieved in this transformation due to the hitherto unreported use of methylacetoin, whose activation occurs with elimination of unreactive acetone. In addition, some of the reaction products were formed with opposite stereochemistry compared to that obtained using other ThDP-dependent enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…[24] As a logical extension of that study on the formal aldehyde-ketone cross-carboligation reaction, we planned to examine the efficiency of the Ao:DCPIP OR-methylacetoin enzyme-substrate pair in the mixed benzoin-like reaction with aromatic aldehydes to access the class of valuable phenylacetyl carbinols, eventually with unusual (S)-configuration. Gratifyingly, condensation of methylacetoin (3) with benzaldehyde (5) under similar conditions to those previously described for the synthesis of chiral tertiary alcohols 4 [24] [3 (20 mM), 5 (20 mM), phosphate buffer pH 6.5 (50 mM), DMSO (10% v/v), MgSO 4 (0.9 mM), ThDP (0.4 mM), purified and lyophilized Ao:DCPIP OR 0.5 mg mL −1 , 30 °C, 12 h], afforded the enantioenriched (S)-1-hydroxy-1- The (S)-configuration of 6 was further confirmed by comparison with an authentic sample of (R)-PAC prepared using the highly (R)-selective cyclohexane-1,2-dione hydrolase (CDH). [25] Hence, the first important result of this explorative study was the confirmation of Ao:DCPIP OR peculiarity to promote, in some occasions, carboligations with opposite stereochemical outcome compared to other wt ThDPdependent enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations